2020
DOI: 10.3390/foods9030362
|View full text |Cite
|
Sign up to set email alerts
|

Are Faba Bean and Pea Proteins Potential Whey Protein Substitutes in Infant Formulas? An In Vitro Dynamic Digestion Approach

Abstract: Infant formulas (IFs) are used as substitutes for human milk and are mostly based on cow milk proteins. For sustainability reasons, animal protein alternatives in food are increasingly being considered, as plant proteins offer interesting nutritional and functional benefits for the development of innovative IFs. This study aimed to assess how a partial substitution (50%) of dairy proteins with faba bean and pea proteins influenced the digestibility of IFs under simulated dynamic in vitro digestion, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 69 publications
0
18
1
Order By: Relevance
“…Nosworthy et al, (2018) reported an increase in sulfur AA after a cooking process. Another study on the protein quality of fava bean ( Le Roux et al, 2020 ) reported an essential AA score higher than in our study (83); however, the limiting amino acid was tryptophan.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…Nosworthy et al, (2018) reported an increase in sulfur AA after a cooking process. Another study on the protein quality of fava bean ( Le Roux et al, 2020 ) reported an essential AA score higher than in our study (83); however, the limiting amino acid was tryptophan.…”
Section: Resultscontrasting
confidence: 93%
“…This effect is consistent with our results, as the extraction of polyphenols in NPP increased significantly (ρ < 0.05) by ∼ 6% digestibility. Le Roux et al, (2020) compared digestibility through in vitro dynamic digestion of two protein concentrates of bean and peas without polyphenols, reporting in vitro protein digestibility of 91.1 ± 3.1 and 74.9 ± 6.7%, respectively. It also has been reported that the digestibility of the fava bean concerning other legumes depends on the albumin content because this protein fraction of plant foods has higher CYS content.…”
Section: Resultsmentioning
confidence: 99%
“…The dry residue from the vacuum flask was dissolved in 5 mL of citrate buffer pH 2.2. The prepared sample was dispensed onto the amino acid analyzer column [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several plants have been suggested as potential suitable protein sources for new infant formulas, these being quinoa [ 374 ], pea [ 375 , 376 , 377 ], faba bean [ 375 , 376 , 377 ], lentil [ 378 ], potato [ 376 , 379 ], and chickpea [ 380 , 381 ], as shown on Figure 5 . Nevertheless, before any of these plant-based protein sources can be used in infant formulas, they would need to comply with the Regulation EU 2016/127 [ 114 ], and for some, they may even be regarded as novel foods, as new processing procedures may be a necessity to provide protein isolates and hence require an EU authorisation as a novel food [ 382 ].…”
Section: Plant-based Infant Formulasmentioning
confidence: 99%
“…The legume faba bean is also known as fava bean or broad bean. In studies of partial substitution of cow’s milk proteins with faba bean proteins in infant formulas [ 375 , 376 , 377 ], it was reported that physicochemical properties of the formula were affected to some degree by the protein substitution [ 377 ]. It was shown that the digestibility of the formula was higher by substituting 50% of the cow’s milk proteins with faba bean protein in a dynamic in vitro model [ 375 ], whereas there were no significant differences observed in a static in vitro digestion model [ 376 ].…”
Section: Plant-based Infant Formulasmentioning
confidence: 99%